Stable carbon isotope variability associated with taxonomic composition of lotic benthic algae. Issue 1 (29th August 2013) - Abe, Shin‐ichiro; Sakano, Hiroyuki; Kobayashi, Sho; Kitano, Satoshi
Summary We examined the relationship between the δ13C and taxonomic composition of benthic algae collected from a riffle (fast current habitat) of a non‐shaded mountain stream, which is a tributary of the Kiso River, Japan. The benthic algal δ13C ranged from −20.6 to −14.2‰ and tended to be 13C‐depleted with increasing relative abundance of upright filamentous cyanobacteria and 13C‐enriched with increasing relative abundance of prostrate filamentous cyanobacteria. Using isotopic mass balance equations, the relative abundance of the dominant taxa, upright and prostrate filamentous cyanobacteria, small diatoms and others, explained 74% of δ13C variability. This study shows a case where the difference in taxonomic composition is a possible source of the isotopic variability of benthic algae, which is a mixture of taxa with distinct isotopic signatures.